Biology of fertility, acclimatization of sheep breed at different heights - Monge Cassinelli, Luis (1953)
Every year the government and sheep farmers imported, mainly from Chile, to improve the herds grazing in the highlands of the Andes, which is a significant sum of money which strongly affects the economy of the herds in the region. It was therefore necessary to study results obtained from these imports and if possible give new insights to make better use of the imported cattle.